2015
DOI: 10.1038/srep17311
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Imprinted Methylation Errors in Human Preimplantation Embryos

Abstract: Assisted reproductive technologies (ARTs) represent the best chance for infertile couples to conceive, although increased risks for morbidities exist, including imprinting disorders. This increased risk could arise from ARTs disrupting genomic imprints during gametogenesis or preimplantation. The few studies examining ART effects on genomic imprinting primarily assessed poor quality human embryos. Here, we examined day 3 and blastocyst stage, good to high quality, donated human embryos for imprinted SNRPN, KCN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 55 publications
4
58
0
Order By: Relevance
“…Specifically, idiopathic male infertility has been strongly associated with methylation defects in H19/IGF2 :IG‐DMR and MEST imprinting loci [Poplinski et al, ], which could potentially explain the increase of methylation defects in children born by ART. In contrast, another study showed that embryos from male factor infertility patients using donor sperm harbored aberrant methylation, suggesting errors in these embryos cannot be explained by infertility alone [White et al, ]. This suggested that ART human preimplantation embryos possess a high frequency of imprinted methylation errors.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, idiopathic male infertility has been strongly associated with methylation defects in H19/IGF2 :IG‐DMR and MEST imprinting loci [Poplinski et al, ], which could potentially explain the increase of methylation defects in children born by ART. In contrast, another study showed that embryos from male factor infertility patients using donor sperm harbored aberrant methylation, suggesting errors in these embryos cannot be explained by infertility alone [White et al, ]. This suggested that ART human preimplantation embryos possess a high frequency of imprinted methylation errors.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent work has shown that high-quality human embryos generated from ART exhibit a high degree of DNA methylation errors in imprinted loci (50). Enrichment of imprinted genes was observed in the set of differentially methylated genes when comparing ICSI (FH and FZ) with the IUI control (Supplemental Table 8), with hypomethylated genes contributing strongly to this enrichment (Supplemental Tables 9 and 10 and Supplemental File 3).…”
Section: Imprinted Genes Are Differentially Methylated In Iui and Icsmentioning
confidence: 98%
“…The cause for the absence or loss of methylation at KvDMR1 is not clear but presumably results from improper establishment and/or maintenance during oogenesis or failure of maintenance after fertilization. KvDMR1 may be particularly susceptible to epigenetic disruption, as evidenced by frequent disruption of methylation following assistedreproductive technologies (Amor and Halliday, 2008;Weksberg et al, 2007;White et al, 2015).…”
Section: Introductionmentioning
confidence: 99%